2022
DOI: 10.3390/horticulturae8040309
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Chemical Characteristics of Sambucus nigra L. Blossom from Different Regions in Bulgaria

Abstract: The aim of the current study was to investigate some bioactive compounds from Sambucus nigra L. blossoms and to evaluate the antioxidant potential of the obtained extracts. In this study, samples from four different regions of Bulgaria /Rhodopes, Plovdiv, Strandzha and Dobrich region/ from Sambucus nigra L. were collected and analyzed for total phenols, flavonoids, sugars and amino acids. The antioxidant activity of the extracts was evaluated by four assays based on different mechanisms. The sweetness index an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The values recorded in the present study are consistent with those reported in other studies published in the scientific literature, namely Tabaszzewska and Sikora [25] reported in their study on composition and antioxidant properties of Sambucus nigra L. extracts, a polyphenol content of 2072.50 mg for the extract obtained from the fresh plant, 619.04 mg for the extract obtained from the frozen plant, 2813.32 mg for the extract obtained from the air-dried plant, and 4070.35 mg for the extract obtained from the lyophilization plant. Mikulic-Petkovsek et al [26] reported for flowers of different elderberry species or interspecific hybrids a total polyphenol content between 7410 and 40,137 mg GAE/kg d.w. and Gentsgevva et al [27] reported a polyphenol content between 299.3 and 49.2 mg GAE/g d.w. Regarding the influence of the extraction method, Horablaga et al [17], who analyzed the influence of the sample preparation/extraction method on the phytochemical profile and antimicrobial activities of 12 commonly consumed medicinal plants, recorded results similar to those reported in the present study, i.e., the highest values being recorded for extracts obtained by microwave, followed by extracts obtained by ultrasound and finally extracts obtained by the conventional method.…”
Section: Antioxidant Profile Determination Of Total Polyphenols Contentmentioning
confidence: 94%
“…The values recorded in the present study are consistent with those reported in other studies published in the scientific literature, namely Tabaszzewska and Sikora [25] reported in their study on composition and antioxidant properties of Sambucus nigra L. extracts, a polyphenol content of 2072.50 mg for the extract obtained from the fresh plant, 619.04 mg for the extract obtained from the frozen plant, 2813.32 mg for the extract obtained from the air-dried plant, and 4070.35 mg for the extract obtained from the lyophilization plant. Mikulic-Petkovsek et al [26] reported for flowers of different elderberry species or interspecific hybrids a total polyphenol content between 7410 and 40,137 mg GAE/kg d.w. and Gentsgevva et al [27] reported a polyphenol content between 299.3 and 49.2 mg GAE/g d.w. Regarding the influence of the extraction method, Horablaga et al [17], who analyzed the influence of the sample preparation/extraction method on the phytochemical profile and antimicrobial activities of 12 commonly consumed medicinal plants, recorded results similar to those reported in the present study, i.e., the highest values being recorded for extracts obtained by microwave, followed by extracts obtained by ultrasound and finally extracts obtained by the conventional method.…”
Section: Antioxidant Profile Determination Of Total Polyphenols Contentmentioning
confidence: 94%
“…Its medicinal properties are recognized worldwide, and it is included in the pharmacopeias of several countries, including the European pharmacopeia [ 15 ]. Black elder is a deciduous shrub or tree between 4 and 12 m, which is widely distributed across Europe, western and central Asia, northern Africa, and North America [ 16 , 17 , 18 ]. It blooms between May and June with white-cream or greenish-yellow flowers, gathered in flat, complex, umbrella-like umbels [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Black elder is a deciduous shrub or tree between 4 and 12 m, which is widely distributed across Europe, western and central Asia, northern Africa, and North America [ 16 , 17 , 18 ]. It blooms between May and June with white-cream or greenish-yellow flowers, gathered in flat, complex, umbrella-like umbels [ 17 ]. Fruits are fleshy with a black-purple color and shiny skin.…”
Section: Introductionmentioning
confidence: 99%
“…The health benefits of the different parts of the S. nigra plant have been investigated by different authors. It has been found that elder flowers are antipyretic, diaphoretic, emetic, expectorant, anti-inflammatory, immunostimulant, antiviral, and antibacterial, while the leaves are disinfectant, diuretic, laxative, purify the blood, and have detoxifying properties [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%